Leaders among the leaders in economics - Molina, José Alberto,Iñiguez, David,Ruiz, Gonzalo,Tarancón, Alfonso (Global Labor Organization (GLO), 2020)
We analyse the production and networks of Nobel laureates in Economics, employing the Normalized Impact Factor (NIF) of their publications in the Journal of Citation Report (Economics), to identify the academic leaders among those laureates awarded between 1969 and 2016. Our results indicate that direct collaborations among laureates are, in general, rare, but when we add all the co-authors of the laureates, there appears a very large component containing 70% of the nodes, so that more than two thirds of the laureates can be connected through only two steps. Deaton, Tirole, Arrow, and Stiglitz are identified as leaders according to the total production of their respective networks.
10419/216772
Keywords: Graue Literatur; Nobel prize; Economics; Impact factor; Research production; Complex networks